2012
DOI: 10.1002/ejic.201101343
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Insertion of Dialkynylphosphanes into the M–C Bond of Cyclopalladated Rings through Activation by Cyclometallated Amines

Abstract: A series of chiral ortho‐platinated and ‐palladated complexes derived from N,N,α‐trimethylbenzylamine has been prepared. The dialkynylphosphane PhP(C≡CMe)2 coordinated regiospecifically as a P→M monodentate ligand to these cyclometallated units in the positions trans to the nitrogen donors of the metallacycles. Upon introduction of selected chirality on the benzylamine unit and subsequent monitoring by using NMR spectroscopy, the P→Pt bond was found to be thermodynamically stable and kinetically inert. The P→P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…À and Cl À , and even the other analogous organic carboxylates, such as O-CH 3 -C 6 H 5 COO À , m-CH 3 -C 6 H 5 COO À , p-CH 3 C 6 H 5 COO À , picolinate, nicotinate and isonicotinate. 55 In other study, a research group proposed a rational approach to synthesize MOFs that include OH À ions based on salt inclusion into alkaline-stable MOFs. Thus, they chose ZIF-8 (as the mother framework) and reported a novel MOF containing hydroxide ions (NBU 4 ) m (A) n {Zn(mim) 2 } 6 (9).…”
Section: Anion-exchangementioning
confidence: 99%
“…À and Cl À , and even the other analogous organic carboxylates, such as O-CH 3 -C 6 H 5 COO À , m-CH 3 -C 6 H 5 COO À , p-CH 3 C 6 H 5 COO À , picolinate, nicotinate and isonicotinate. 55 In other study, a research group proposed a rational approach to synthesize MOFs that include OH À ions based on salt inclusion into alkaline-stable MOFs. Thus, they chose ZIF-8 (as the mother framework) and reported a novel MOF containing hydroxide ions (NBU 4 ) m (A) n {Zn(mim) 2 } 6 (9).…”
Section: Anion-exchangementioning
confidence: 99%
“…From the literature reviews, it is also clear that these chiral auxiliaries are stable and that they are not directly involved in any chemical transformations and thus retain their structural and stereochemical integrity. In our recent effort to search for new chiral cyclometalated complexes as catalysts for asymmetric hydrophosphination reactions, however, we observed that the aromatic carbon–palladium bonds in ortho -palladated benzylamine complexes are indeed chemically reactive, as they undergo insertion reactions in the presence of coordinated alkynylphosphines. , On the other hand, the carbon–platinum bonds in the analogous ortho -platinated complexes are completely unreactive toward similar insertion reactions . Upon closer examination of the chemical behavior of these ortho -platinated benzylamine complexes, interestingly, we discovered that the organometallic chelates themselves can be activated by the presence of external platinum ions toward the aforementioned carbon–carbon bond formation.…”
Section: Introductionmentioning
confidence: 98%
“…Surprisingly, this simple ppo ligand has never been applied for the construction of 2D Hofmann SCO frameworks to date, although some ppo-based complexes with Cd 2+ and Cu 2+ ions have been reported. 36,37 Herein, three novel isostructural 2D Hofmann SCO frameworks: [Fe(ppo) 2 M(CN) 4 ] (1, M = Pt 2+ ; 2, M = Pd 2+ ; 3, M = Ni 2+ ) have been successfully constructed by using ppo as the axial ligand. These frameworks have been fully characterized by elemental analysis, Fourier transform infrared (FT-IR), thermogravimetric analysis (TGA), powder X-ray diffraction (PXRD) and single crystal X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%